Evaluation of human leukocyte antigen class-II DRB1 & DQB1 and its association with cervical carcinoma - Mriganka Mouli Saha; Nayan Chandra Sarkar; Debarati Saha; Madhumita Mukhyopadhyay; Subhash Chandra Biswas; Pradip Kumar Mitra (Al Ameen Medical College, 2019)
Background: Cervical Carcinoma is the second most leading carcinoma following breast cancer among Indian women. It has been showed that HLA class II DQ is associated in persistent HPV infection and HLA class II DR is responsible for increased clearance of HPV virus from cervix. Methodology: In this study we had included total 96 women (53 women in the control, 31 women in CIN group, and 12 women in cervical carcinoma (CC) group. Result: Our study showed that HLA DRB1 was associated with the healthy and cervical intraepithelial neoplasia population; whereas HLA DQB1 was associated with the invasive cervical carcinoma. Conclusion: HLA DRB1 and HLA DQB1 is useful tool for community based screening and focused HPV vaccination among the risk group to prevent the invasive cervical cancer.